Leaf-surface wax extracted from different pines as green additives exhibiting excellent tribological properties. (15th November 2017) - Feng, Xin; Cao, Zhengfeng; Xia, Yanqiu
Abstract: Given the increasing attention on the topic of the 'Green chemical', it is imperative to explore new environmental friendly and biodegradable lubricants to meet the tribological performances and environmental needs. In this work, three types of leaf-surface wax were extracted from different pines as green lubricant additives and their chemical compositions, friction reduction and anti-wear abilities were investigated in detail. The results show that the leaf-surface wax extracted from different pines as additives in synthetic ester exhibit superior friction reduction and anti-wear abilities for steel/steel and steel/aluminum pairs. Based on the scanning electron microscopy and time-of-flight secondary ion mass spectroscopy analysis, the preferable tribological performances are ascribed to the physical adsorption film and tribo-chemical reaction film generated by the leaf-surface wax on the worn surfaces during the sliding process.